If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4z = 51 Solving 9 + -4z = 51 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4z = 51 + -9 Combine like terms: 9 + -9 = 0 0 + -4z = 51 + -9 -4z = 51 + -9 Combine like terms: 51 + -9 = 42 -4z = 42 Divide each side by '-4'. z = -10.5 Simplifying z = -10.5
| 4.824-5= | | 12-4x=-2x-2 | | 8+a=2a-2-3a | | 4(y-1)=24 | | 144554=2141534 | | 6m-8+2=9m-1 | | 2.5-x=3.5 | | y^2=x+2 | | 8w*3=152 | | -6=.75(y+2) | | 0.6k+5=7 | | -1=9-.666x | | 52.5(3-x)=315 | | (8)+(-1)= | | 175(n-2)=700 | | ab+c= | | -1=9-.33x | | 9x-15=30+4x | | 1x-21=-8 | | 12x^2-21x-45=0 | | -8x+80=-4x+44 | | 8s-20=32+6s | | 3b+b=16 | | 9+xy= | | 4*4+10y=40 | | 4z+3=23 | | 5p-6+p=14-2p | | 6x-31=4x-19 | | 56=8+3(y+4) | | 2x-7=5+x | | 11(a+b)= | | v=lwh*w |